The teacher performance evaluation in learning management in inclusive settings - Hermanto Hermanto (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2022)
This study is to evaluate the performance of basic education teachers in managing learning in inclusive settings, with a focus on teachers' understanding of the diversity of students with special needs, teachers' abilities in preparation for learning in inclusive settings, teachers' abilities in implementing inclusive setting learning and teachers' abilities in assessing learning in inclusive settings. This descriptive study is based on monitoring and evaluation data for inclusive schools in 2019. The research subjects involved 160 teachers, consisting of 21 early childhood education teachers, and 139 elementary school teachers from five districts in Daerah Istimewa Yogyakarta (DIY) Province. The data collection instrument used a questionnaire, while the data analysis technique used descriptive analysis. The results of this study conclude that teachers whose performance is effective at the level of inclusion are teachers who understand the conditions and development of their students. Based on the evaluation of teacher performance, it is necessary to provide teacher strengthening programs in line with inclusive education policies, and appropriate accommodation for students with disabilities in schools.